The Accounting Reform in Russia. How to Teach Economists? - ProsvirinaIrina; IvanovAleksey; ZaionchikLeonid Zaionchik (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2021)
Most post-socialist countries harmonize national accounting standards with IFRS. Many countries are also characterized by a simultaneous use of both national and international standards. The same goes for Russia. Deep reform of national standards has entered an active phase: annually, starting from 2018, several new standards harmonized with the international ones have been introduced. At the same time, former standards remain in force. In such conditions, the process of teaching students majoring in accounting must consider these peculiar features. In the article, we analyze the existing teaching methods and conclude that they are generally focused only on the study of the existing national accounting standards. However, working at enterprises requires knowledge and ability to apply both the existing standards and the standards which will be introduced in the coming years. It is also necessary to know international standards as a methodological basis applied when a matter is not regulated by the national standards. The article highlights the experience of South Ural State University. Since 2016, it has been creating a methodology of intensive teaching bachelors of economics majoring in “Accounting, Analysis and Audit”. The methodology is based on the development of a set of professional competencies intoa set of learning outcomes as more appropriate for the tasks of such teaching. It is characterized byan emphasis on the students’ research and analytical work. Its implementation results in the appearance of a specialist who is quickly adapted to work in large companies. The methodology is applicable in all university departments teaching accounting to bachelors.